Experimental Study of a Silica Sand Sensible Heat Storage System Enhanced by Fins - Paniz Niksiar; Claire Rogillio; Hamid Torab; Saeed Tiari (Energies)
This study aims to assess the thermal performance of silica sand as a heat storage medium within a shell-and-tube sensible heat storage thermal energy system that operates using water as the heat transfer fluid. Two types of silica sand were analyzed, fine sand and coarse sand, to determine which was the best for heat transfer and storage. It was found that the fine sand, which had smaller particles compared to the coarse sand, enhanced the heat transfer in the system. The fine sand required 11.86 h to charge using the benchmark case and 17.58 h to discharge, whereas the coarse sand required 13.36 h to charge and 16.55 h to discharge. Methods of enhancement are also explored by comparing the system performance with the inclusion of four different configurations of copper fins to investigate against a benchmark case without fins in the system with fine sand. When equipped with four radial fins, the system demonstrated a significant enhancement, reducing charging and discharging times by 59.02% and 69.17%, respectively, compared to the baseline. Moreover, the system exhibited an even greater improvement with eight radial fins, cutting charging and discharging times by 63.74% and 78.5%, respectively, surpassing the improvements achieved with four radial fins. The ten annular fins decreased the charging time by 42.58% and the discharge by 62.4%, whereas the twenty annular fins decreased the charging by 56.24% and the discharging by 68.26% when compared to the baseline.